SINKRETISME DALAM RITUAL COK BAKAL DAN HUBUNGANNYA DENGAN KEPERCAYAAN MASYARAKAT DESA SUNGAI BAUNG KECAMATAN TALANG UBI KABUBATEN PALI (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2021)
The analysis entitled "Syncretism within the Ritual Cok Bakal and Its Relationship with Community Trust in Sungai Baung Village, Talang Ubi District, Pali Regency. The ritual cok bakal may be a ritual that's allotted at the time of rice harvest, the form of the ritual cok may be a banana leaf shaped in a very instrumentation that is then full of varied herbs or room spices which is able to later be placed within the corner of the garden that is then browse out with a prayer. prayers that are studied by elders for a protracted time. The ritual cok bakal may be a ritual that can't be faraway from the daily activities of the folks of Sungai Baung Village, square measure still maintaining the tradition, during this case, the tradition of constructing cok bakal. Cok bakal are some things that's created to get security and happiness from the almighty. This study aims to work out the syncretism within the ritual cok bakal and its relationship with the beliefs of the folks of Sungai Baung Village, Talang Ubi District, Pali Regency. this sort of analysis is allotted by means that of (file analysis) field research with qualitative knowledge varieties. Sources of knowledge used square measure primary data obtained directly by observant and interviewing sure elders or residents believe the ritual cok bakal directly, and secondary knowledge obtained from supply documentation derived from documentation and books as quotations obtained, from libraries, journals and also the internet.